The impact of Appleton's model on interactive thinking and learning the skills of the short serve and the forehand stroke in badminton for female students. - Shaker, L.Dr. Lubna Abdul Rasoul; Qasim, Asst.L.Abtgha Mohammed; Baqir, Asst.L.Mona Ihsan Muhammad (Sulaimani Journal for Humanities, 2026)
He modeled (Apleton) a model of teaching that relies on knowledge and relies on the theory of knowledge and supports theories that can explain the appearance of knowledge. The letter is aimed at measuring interactive thinking for second year students in the faculty of physical education and sports sciences of Karbala University, and educational units association Learning Appleton in Interactive Thinking and Skills Learning Skills Sending Small Scales and Putting Image Dimensions by Airline for Students , Introduction to the Impact of Modeling Appleton in Interactive Thinking and Knowledge is the skill of sending the shortcut and striking the dimensions of the Imam, and recognizing the best of the official and experimental groups in interactive thinking and knowledge Skill for the field of deficiency and multiplier dimensions use experimental research methodology and which includes the nature of the research problem intended to solve and design the combined sets Office and Experiment, Preliminary and Longitudinal Experimental Studies, and includes research group for second year students in the Faculty of Physical Education and Sports Sciences - University of Karbala For the academic year (2024-2025) and the number of adults (164) students are divided into academic groups A, B, C, E, F, D)) The main research eye is (A,C), it includes branch (A) the experimental group and branch (C) the administrative group. 30 students were selected to represent the main research group, 15 students were selected in the experimental group and 10 students were selected as the research group It was randomly sampled, and the proportion of the main eye (17,24 %) of the original population was added, and I conducted detailed experiments for study and communication The statistical results were analyzed using statistical software (SPSS). The study reached the set of results to demonstrate the positive effect of Appleton in promoting the equality of the experimental set of students in interactive thinking and skill learning Larsal القصير وضربة الابعاد الامامية بالريشة الطائرة